Topical Transplantation of Bone Marrow Mesenchymal Stem Cells Made Deeper Skin Wounds Regeneration. Issue 1 (February 2022) - Yonghong, Qin; Aishu, Li; Al-Ajam, Yazan; Yuting, Liao; Xuanfeng, Zhang; Jin, Zhang
Current wound healing models generally employ full-thickness or irregular split wounds. Consequently, assessing the type of healing at varying wound depths and determining the deepest level at which wounds can regenerate has been a challenge. We describe a wound model that allows assessment of the healing process over a continuous gradient of wound depth, from epidermal to full-thickness dermal loss. Further, we investigate whether green fluorescent protein–labeled bone marrow mesenchymal stem cells (BM-MSCs/GFP) transplantation could regenerate deeper wounds that might otherwise lead to scar formation. A wound gradient was created on the back of 120 Sprague Dawley rats, which were randomized into the BM-MSCs/GFP and control group. These were further subdivided into 6 groups where terminal biopsies of the healing wounds were taken at days 1, 3, 5, 7, 14, and 21 post-operatively. At each observed time point, the experimental animals were anesthetized and photographed, and depending on the group, the animals euthanized and skin taken for rapid freezing, haemotoxylin and eosin staining, and vascular endothelial growth factor (VEGF) immunohistochemistry. We found the deepest layer to regenerate in the control group was at the level of the infundibulum apex, while in the BM-MSCs/GFP group this was deeper, at the opening site of sebaceous duct at hair follicle in which had the appearance of normal skin and less wound contraction than the control group ( P value less than .05). The expression of VEGF in BM-MSCs/GFP group was higher than that in control group ( P value less than .05). The number of vessels increased from 2.5 ± 0.2/phf of control group to 5.0 ± 0.3/phf of BM-MSCs/GFP ( P value less than .05). The progressively deepening wound model we described can identify the type of wound repair at increasing depths. Further, topical transplantation of BM-MSCs/GFP significantly improved regeneration of deeper wounds from infundibulum apex (maximum depth of control group regeneration) to the opening site of sebaceous duct at hair follicle level.